PTU-006 Large colonic polyps detected during bowel cancer screening—a retrospective review of treatment and outcomes. (23rd September 2015) - Fellows, H; Meagher, U; Tighe, R
Abstract : Introduction: Bowel cancer is the third most common cancer in the UK, with approximately 16 100 deaths per annum. The Norfolk and Norwich University Hospital was one of the first sites in the country to introduce the bowel cancer screening (BCS) programme. It offers men and women aged between the ages of 60 and 69 an initial screening via a faecal occult blood test. Those with an abnormal result are then offered a colonoscopy. Large (>2 cm) polyps are uncommon in routine practise however with the development of the BCS programme are now more readily encountered. Methods: To assess the success and safety of endoscopic resection of large (>2 cm) colorectal polyps in the context of the BCS programme. Records of all patients who had a polyp >2 cm were identified using the BCS database. We analysed data from a 3-year period starting from July 2006 until July 2009. We looked at polyp location, morphology, completeness of resection, complications and histological staging. Results: 135 polyps >2 cm were detected in 127 patients with a mean size of 3 cm (spread 2–7 cm). 17.8% (24/135) were thought to be invasive by the endoscopist and all of these were biopsied. 12.5% of these biopsied polyps were found to be adenocarcinoma/carcinoma in situ. 11.9% (16/135) of all polyps were adenocarcinoma. 31.9% (43/135) of polyps were sessile, and 68.9% (92/135) were pedunculated. 94.1% (127/135) of polyps were left sided. 82.2% (111/135) of polyps were removed at the time of the initial endoscopy. Of these 22.5% were sessile and 77.5% pedunculated. 20% of the sessile polyps had further treatment by means of either surgery (12%, 3/3 benign disease) or repeat polypectomy (8%) for residual polyp tissue. In comparison 8.1% of pedunculated polyps went on to have either surgery (5.8%, 4/5 adenocarcinoma) or repeat polypectomy (2.3) for residual polyp tissue. There were no carcinomas detected in those polyps measuring >5 cm. However the greatest percentage of adenocarcinomas were found in pedunculated polyps measuring 4049 mm. Three patients required endoscopic therapy for bleeding at the time of polypectomy and two patients were admitted as a precaution. Three patients had immediate bleeding following polypectomy which was controlled endoscopically at the time of initial endoscopy. Two of these patients were admitted overnight as a precaution. There were no cases of perforation, no late bleeds and no readmissions. Conclusion: Our series demonstrates that endoscopic therapy for large pedunculated and sessile colorectal polyps is a safe and effective treatment with minimal morbidity and no mortality. We found that despite experienced endoscopists performing colonoscopy it was difficult to predict which polyps are malignant. However large pedunculated polyps seem to carry a significant malignant potential.